Hepatitis B Virus Reactivation in Patients With HBV-Related Advanced Hepatocellular Carcinoma Undergoing Lenvatinib and Camrelizumab Treatment - Bi Sheng MD; Dong Wang MD; Jingjing Wang MD (Cancer Control)
Objective This study aimed to evaluate hepatitis B virus (HBV) reactivation and its effect on tumor response and survival outcomes in patients with HBV-related advanced hepatocellular carcinoma (HCC) undergoing lenvatinib plus camrelizumab treatment. Methods 216 patients with HBV-related advanced HCC receiving lenvatinib and camrelizumab were enrolled. Overall survival (OS), progression-free survival, and tumor response were evaluated. Univariate and multivariate analyses were performed to determine risk factors for HBV reactivation. Results HBV reactivation occurred in 24 patients (11.1%). It was associated with poor survival and tumor response in these patients. Undetectable DNA levels, the absence of antiviral therapy, and high ALT levels were identified as vital risk factors for HBV reactivation. After receiving or adjusting the antiviral strategy, tumor response improved in patients with HBV reactivation. Conclusions HBV reactivation could occur in patients with HBV-related HCC, treated with lenvatinib and camrelizumab, worsening tumor response and patient survival. Regular monitoring of the indicators of HBV infection and effective antiviral treatments are recommended for these patients to prevent severe complications.